MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATERI KOLOID MELALUI MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) BAGI KELAS XI IPA DI SMA YPPKK MORIA KOTA SORONG TAHUN 2020 - Lidiana Tupa Sulorante (SOSCIED, 2023)
This study aims to determine the increase in activities and learning outcomes of colloidal nateri for students of class XI IPA SMA YPPKK Moria through the cooperative learning model Teams Games Tournament (TGT). This type of research is classroom action research (Classroom Action Research) which is carried out collaboratively between researchers and teachers. Research is carried out in two cycles, each cycle consists of four components, namely planning, action, observation and reflection. Data collection techniques and tools used in this study were interviews, observations, documentation and tests. Data analysis is carried out in 3 stages, namely reduction, presentation of data and drawing conclusions. The results of the study found that the Teams Games Tournament cooperative learning model was effective in increasing student learning activities. In this study, the implementation of the TGT model was able to encourage active participation of students in the learning process of colloidal material because this model involves teamwork, group games and tournaments that produce a fun and interactive learning atmosphere. The use of this learning model can also significantly improve students' understanding and mastery of colloidal material because student involvement in games and teamwork helps students acquire better knowledge and encourages the achievement of higher learning outcomes.